The magical reality of Nadia - Youssef, Bassem; Daly, Catherine R.; Holgate, Douglas (New York Scholastic Inc., 2021)
Competing to design a new exhibit for the local museum, a sixth grade Egyptian immigrant is teased about her heritage by a newcomer, before an ancient amulet she wears imparts a hilarious and helpful secret.
ALA Booklist
620
4.5
3-6
Accelerated Reader
Keywords: Egyptian Americans -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Contests -- Fiction; Magic -- Fiction; Egyptian Americans -- Fiction; Middle schools -- Fiction; School stories; Contests -- Fiction; Magic -- Fiction; Humorous fiction